The biogenesis and function of nucleosome arrays - Ashish Kumar Singh (Nature Portfolio, 2021)
Nucleosomes form arrays with even spacing between them in virtually all eukaryotes; however, their biogenesis is incompletely understood. Here the authors show that nucleosome density and DNA sequence along with the Ino80 chromatin remodeling complex play a role in nucleosome array formation in yeast and that the transcriptional machinery disrupts evenly-spaced nucleosomes.